Successful separation of Xipho-Omphalopagus twins - Oak S; Joshi R; Parelkar Sandesh; Bhat Uday; Satish Kumar K (Wolters Kluwer Medknow Publications, 2007)
Xipho-omphalopagus twins are conjoined twins sharing some part of gastrointestinal system and lower sternum. These types of twins have best chances of survival if successfully separated. We report a case of successfully separated Xipho-omphalopagus twins, highlighting the importance of proper planning and team effort in such separations.